Food governance for better access to sustainable diets: A review - del Valle M, Martín; Shields, Kirsteen; Alvarado Vázquez Mellado, Ana Sofía; Boza, Sofía (Frontiers in Sustainable Food Systems, 2022)
‘Governance’, understood as organizational governance, is essential to more sustainable food provisioning systems ensuring sustainable health, heritage and natural environments. Governance enables regional and local perspectives to be aligned with commitments from national and international organizations. Within the wealth of scholarship on food systems governance, agricultural governance and agency is a rarely interrogated dimension, despite the clear impacts of agricultural decisions on health and environmental outcomes. In this paper we discuss the findings of a scoping review on the implications of food governance and its relation to sustainable diets, meaning diet that protect health, cultures and the natural environment.